Thermo-mechanical Analysis of Cross ply and Angle ply Laminated Composite Plates - Joshan, Yadwinder Singh (My University, 2017)
In the present work, the closed form solutions for thermo-mechanical response characteristics of cross-ply and static response characteristics angle-ply plates are developed. The laminated composite plates are modelled in an axiomatic framework based on an inverse hyperbolic shear deformation theory (IHSDT). The principle of virtual work is used to obtain the governing differential equations. The governing differential equations are solved separately for cross-ply and angle-ply plates by consideration of stiffness characteristics of these plates. The sinusoidal and uniform transverse mechanical loading is considered with the linear and non-linear variation of temperature field across the thickness of the plate. The composite plates with simply supported boundary conditions are considered and Navier solutions satisfying the associated boundary constraints are developed. Due to the limitation of applicability of closed form solution only to the simply supported case, the laminated plates are modelled in finite element framework using the potential energy approach. The convergence and accuracy of finite element solution is compared with the closed form solution. The thermo-mechanical response characteristics of cross-ply and static response characteristics angle-ply plates under various boundary conditions are investigated and the results are presented in the non-dimensional form. The obtained results are compared with the existing results for a variety of examples and based on this comparison study, the validity, applicability and accuracy of IHSDT for such analysis is ensured. It is observed from the results that IHSDT can be accurately applied for thermo-mechanical responses of laminated composite plates. The effects of span thickness ratio, boundary conditions, material anisotropy ratio, lamination sequence, loading and thermal conditions, and aspect ratio on the thermo-mechanical response characteristics are also concluded.
Master of Engineering-CAD/CAM
Keywords: Laminated composite plates; Thermo-mechanical analysis; Cross-ply and angle-ply plates; Navier solution; Finite element method; Shear deformation theory